(untitled) (Biocenosis, 2022)
Numerous people, inside and outside Costa Rica, refer to Dr. Mario Boza, and justifiably so, as "the national parks’ father", a context in which he is considered to be someone fully dedicated to nature conservation. This is all very good, except for those who think he was one of those "conservationists at all costs" who confuse conservation with "hands off". Nothing could be further from the truth. He was fully convinced that, in order to succeed and have a future, nature protection had to prove that, instead of being a burden on the State it could lead to a rational and productive use of natural resources; not only through the constant supply of environmental services fundamental to life such as oxygen, water and the thousands of products we get from plants and animals, but also through its responsible use for amusement and recreation, both for nationals and foreigners.